Pentingnya Bimbingan Belajar Terhadap Peningkatan Kemampuan Berbahasa Indonesia Siswa - Landunau, Imanuel (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2025)
Learning guidance is a process or effort to provide assistance to students in solving learning problems they face, so that desired learning objectives can be achieved. Indonesian language learning guidance is implemented to train students' understanding and proficiency in using the Indonesian language. This study employs qualitative research using a phenomenological approach. Data collection techniques in this research include observation, documentation, and interviews. Based on interview results with informants regarding students' Indonesian language abilities, the author concludes that students' Indonesian language proficiency remains inadequate because they tend to use regional languages and require learning guidance from teachers. After conducting the research, it was found that students' understanding of the Indonesian language is significantly lacking. Students only comprehend lessons when teachers deliver them using regional languages combined with some Indonesian. Therefore, teachers need to implement additional learning activities through Indonesian language learning guidance to help students achieve their desired learning objectives.